Family conversations about species change as support for children's developing understandings of evolution. Issue 3 (16th December 2022) - Hohenstein, Jill; Tenenbaum, Harriet R.
Abstract: To examine the ways that 6‐ to 11‐year‐old children's conversation with their parents support their developing understandings of evolution, 49 parent–child dyads participated in a study with two elicited discussion tasks: origins of species and potential species change. Conversational data were transcribed, coded, and qualitatively and quantitatively analyzed to compare the appearance of reasoning in each type of task. Quantitative analyses revealed correlations between tasks in informed naturalistic reasoning as well as differences in the way reasoning was expressed in each task. In addition, parent–child dyads with older children were more likely to use informed naturalistic reasoning than parent–child dyads with younger children. A subset of the data was analyzed qualitatively and showed that irrespective of how much evolution reference was present in the conversation, parents supported their children's learning through scaffolding. However, greater amounts of nonscientific reasoning appeared in the groups with less evolution talk. This study demonstrates that family talk about evolution varies with context both within and between families.